THE HISTORY OF CREATION AND THE ESSENCE OF THE COMBINED SOILS TESTING OF PENETRATION AND ROTATIONAL CUT METHOD - Zotsenko, M. L. (Academic journal Industrial Machine Building Civil Engineering, 2018)
In the early 1960s, the USSR geotechnicians were given the assignment to develop the non-rock soils strength characteristics determining method in order to enable the operative tracked and wheeled vehicles passage estimation through the cross country. As a result of theoretical justification alongside the approbation in lab and field conditions by the group of professionals, there was developed a new method of soils strength investigation by the way of joint penetration and rotational cut testing. A new method of estimating soils strength undergone the overall investigation in different soils environments of the European part of USSR, particularly in Karelia – on stripped clays, center and the south of Ukraine – on sands and loess loams, Moscow region – on heavy clay soils. The prototype equipment allowed conducting the research in the cross country, shallow water areas, on the river beds and bottoms of the lakes. In 1970 the equipment and methodology of joint penetration and rotational cut testing were used during the Moon surface investigation by Lunokhod-16 apparatus.